Charlemagne and the Lombard Kingdom That Was: the Lombard Past in Post-Conquest Italian Historiography - Fabbro, Eduardo (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
The Carolingian conquest of Lombard Italy (774) was preceded by a massive effort on the part of the Church to convince the Frankish court of the legitimacy of the invasion. Relying on a terminology borrowed from Gregory I, the papal court produced an offensive portrait of the Lombards, depicted as treacherous, vile, and heathen. This article analyzes eighth-century papal epistolary and the Liber Pontificalis in order to establish the strategies behind this campaign. In a second moment, we turn to the Lombard response after the conquest, and the efforts of Paul the Deacon as well as the anonymous author of the Origo Langobardorum codicis Gothanis to question the papal portrait of the Lombards and to reclaim the Christian past of their people. Both Paul and the Gotha Origo focused on the importance of the conversion — and especially the role of Gregory the Great — in the rehabilitation of the Lombards. Their works, this article suggests, represent an attempt of the Lombards to dissociate their Christian faith from the conquest and to reclaim the narrative about their own past.